Exemplos de T-espaços e T-ideais infinitamente gerados - Urure, Ronald Ismael Quispe (Universidade Federal de São Carlos, 2014)
Let F be a field of characteristic p ≥ 3. Denote by F0(X) and F1(X) the free associative algebras without and with unity, respectively, freely generated by the infinite set X. In this dissertation we study T-spaces and T-ideals infinitely generated. In [2] the mathematicians Aladova and Krasilnikov exhibited in F0(X) a T-ideal infinitely generated that contains the polynomial x2p. In [9], the mathematicians Goncalves, Krasilnikov and Sviridova exhibited in Fi(X) limits T-spaces when F is infinite. The objective of this dissertation is to study the results of the two papers cited above.
Keywords: Álgebra; T-ideal; T-espaço; Specht, Problema de; Grassmann, Álgebra de; CIENCIAS EXATAS E DA TERRA::MATEMATICA